Cognitive and Psychological Functioning in Chiari Malformation Type I Before and After Surgical Decompression - A Prospective Cohort Study. Issue 6 (18th October 2021) - Seaman, Scott C; Streese, Carolina Deifelt; Manzel, Kenneth; Kamm, Janina; Menezes, Arnold H; Tranel, Daniel; Dlouhy, Brian J
Abstract: BACKGROUND: Chiari Malformation Type I (CM-I) is defined as cerebellar tonsil displacement more than 5 mm below the foramen magnum. This displacement can alter cerebrospinal fluid flow at the cervicomedullary junction resulting in Valsalva-induced headaches and syringomyelia and compress the brainstem resulting in bulbar symptoms. However, little is known about cognitive and psychological changes in CM-I. OBJECTIVE: To prospectively assess cognitive and psychological performance in CM-I and determine whether changes occur after surgical decompression. METHODS: Blinded evaluators assessed symptomatic CM-I patients ages ≥18 with a battery of neuropsychological and psychological tests. Testing was conducted preoperatively and 6 to 18 mo postoperatively. Data were converted to Z-scores based on normative data, and t -tests were used to analyze pre-post changes. RESULTS: A total of 26 patients were included, with 19 completing both pre- and post-op cognitive assessments. All patients had resolution of Valsalva-induced headaches and there was improvement in swallowing dysfunction ( P < .0001), ataxia ( P = .008), and sleep apnea ( P = .021). Baseline performances in visual perception and construction (z = −1.11, P = .001) and visuospatial memory (z = −0.93, P = .002) were below average. Pre-post comparisons showed that CM-I patients had stable cognitive and psychological functioning after surgery, without significant changes from preoperative levels. CONCLUSION: CM-I patients had below average performance in visuospatial and visuoconstructional abilities preoperatively. Prospective longitudinal data following surgery demonstrated improved neurologic status without any decline in cognition or psychological functioning. Routine pre- and postoperative formal neuropsychological assessment in CM-I patients help quantify cognitive and behavioral changes associated with surgical decompression. Graphical Abstract: